Changing Their Tune: How Consumers’ Adoption of Online Streaming Affects Music Consumption and Discovery - Datta, Hannes; Knox, George; Bronnenberg, Bart J. (Marketing Science, 2018)
Instead of purchasing individual content, streaming adopters rent access to libraries from which they can consume content at no additional cost. In this paper, we study how the adoption of music streaming affects listening behavior. Using a unique panel data set of individual consumers’ listening histories across many digital music platforms, adoption of streaming leads to very large increases in the quantity and diversity of consumption in the first months after adoption. Although the effects attenuate over time, even after half a year, adopters play substantially more, and more diverse, music. Relative to music ownership, where experimentation is expensive, adoption of streaming increases new music discovery. While repeat listening to new music decreases, users’ best discoveries have higher play rates. We discuss the implications for consumers and producers of music. Data and the online appendix are available at https://doi.org/10.1287/mksc.2017.1051 .